A Simple P.P.T Problem.

Geometry Level 3

Let n n and m m be positive integers, where n n is even.

In right A B C \triangle{ABC} one leg is 1 n \dfrac{1}{n} times the sum of the other two sides and the perimeter is m m .

If we multiply each side of right A B C \triangle{ABC} by 2 n ( n + 1 ) m \dfrac{2n(n + 1)}{m} we obtain a primitive pythagorean triple ( a , b , c ) (a^{*},b^{*},c^{*}) .

Find the value of n n for which a + b + c = 10 n 8 a^{*} + b^{*} + c^{*} = 10n - 8 .


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Rocco Dalto
Mar 14, 2020

a = 1 n ( b + c ) a = \dfrac{1}{n}(b + c) and a + b + c = m b + c = m a a + b + c = m \implies b + c = m - a \implies

n a = m a ( n + 1 ) a = m a = m n + 1 b + c = m n n + 1 na = m - a \implies (n + 1)a = m \implies a = \dfrac{m}{n + 1} \implies b + c = \dfrac{mn}{n + 1}

c = m n n + 1 b ( m n n + 1 b ) 2 = m 2 + ( n + 1 ) 2 b 2 \implies c = \dfrac{mn}{n + 1} - b \implies (\dfrac{mn}{n + 1} - b)^2 = m^2 + (n + 1)^2b^2 \implies

( m n ( n + 1 ) b ) 2 = m 2 + ( n + 1 ) 2 b 2 m 2 n 2 2 m n ( n + 1 ) b + ( n + 1 ) 2 b 2 = (mn - (n + 1)b)^2 = m^2 + (n + 1)^2b^2 \implies m^2n^2 - 2mn(n + 1)b + (n + 1)^2b^2 =

m 2 + ( n + 1 ) 2 b 2 m 2 ( n 2 1 ) = 2 m n ( n + 1 ) b m^2 + (n + 1)^2b^2 \implies m^2(n^2 - 1) = 2mn(n + 1)b \implies

b = m 2 ( n 2 1 ) 2 m n ( n + 1 ) = m ( n 1 ) 2 n c = m ( n 2 + 1 ) 2 n ( n + 1 ) b = \dfrac{m^2(n^2 - 1)}{2mn(n + 1)} = \dfrac{m(n - 1)}{2n} \implies c = \dfrac{m(n^2 + 1)}{2n(n + 1)}

( a , b , c ) = ( m n + 1 , m ( n 1 ) 2 n , m ( n 2 + 1 ) 2 n ( n + 1 ) ) \implies (a,b,c) = (\dfrac{m}{n + 1}, \dfrac{m(n - 1)}{2n}, \dfrac{m(n^2 + 1)}{2n(n + 1)})

Multiplying each side by 2 n ( n + 1 ) m \dfrac{2n(n + 1)}{m} we obtain ( a , b , c ) ( 2 n , n 2 1 , n 2 + 1 ) = (a,b,c) \sim (2n, n^2 - 1,n^2 + 1) =

( a , b , c ) (a^{*}, b^{*},c^{*}) and ( n , 1 ) = 1 (n,1) = 1 and n n is even ( a , b , c ) \implies (a^{*}, b^{*},c^{*}) is a primitive pythagorean triple

a + b + c = 2 n 2 + 2 n = 10 n 8 2 ( n 2 ) 2 = 0 n = 2 \implies a^{*} + b^{*} + c^{*} = 2n^2 + 2n = 10n - 8 \implies 2(n - 2)^2 = 0 \implies \boxed{n = 2} .

Jon Haussmann
Apr 21, 2020

We are told that the perimeter of the original triangle is m m . When this triangle is scaled by a factor of 2 n ( n + 1 ) m \frac{2n(n + 1)}{m} , the perimeter becomes 2 n ( n + 1 ) 2n(n + 1) . So 2 n ( n + 1 ) = 10 n 8. 2n(n + 1) = 10n - 8. The solution to this equation is n = 2 n = 2 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...